Pergeseran Otoritas Agama dalam Pembelajaran Al-Qur'an - Tati Rahmayani (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2018)
This paper discusses the shift of religious authority in Al-Qur'an learning. usually, someone who wants to learn to read Al-Qur'an will come to a cleric, or kiyai teacher to teach him to read the Qur'an. however, with current technological advances, religious authorities originally held by ulama or someone who is an expert in the science of religion shifted to other media such as the internet, digital Al-Qur'an or other Al-Qur'an media. In addition, with the advancement of technology, the publishers of the Al-Qur'an have their own innovations to meet the needs of Muslims for children, adults, and even now the Qur'an is available for the diffable. Where there is a pictorial Al-Qur'an for children, the Al-Quran braille for people with disabilities, the Al-Qur'an red pen and the Al-Qur'an tajwid are colored for people who want to study Al-Quran themselves. In addition to the diverse prints of the Koran, there are also online Al-Quran learning sites and other Al-Quran applications both on smartphones and computers. The advancement in technology has made people who want to learn al-Quran easy.